Long‐term results of the MCL01 phase II trial of rituximab plus HyperCVAD alternating with high‐dose cytarabine and methotrexate for the initial treatment of patients with mantle cell lymphoma. (14th May 2020) - Massaro, Fulvio; Stepanishyna, Yana; Manni, Martina; Luminari, Stefano; Galimberti, Sara; Marcheselli, Luigi; Visco, Carlo; Tecchio, Cristina; Stelitano, Caterina; Angrilli, Francesco; Petrini, Mario; Merli, Francesco; et al.
Summary: Mantle cell lymphoma is a rare and incurable lymphoproliferative disorder. In the MCL01 trial, patients were treated with the R‐HCVAD regimen [rituximab plus HyperCVAD (hyperfractionated cyclophosphamide, vincristine, doxorubicin, dexamethasone; R‐CVAD) alternating with high‐dose methotrexate and cytarabine (AM)] for four cycles followed by autologous stem cell transplantation (ASCT) for those who reached only a partial response. After a median follow‐up of 10·5 years, we reported 10‐year progression‐free and overall survival rates of 35% and 61% respectively, with a 10‐years cumulative incidence rate of second malignancies of 10·6%. Mature results of the MCL01 trial confirmed the efficacy of HyperCVAD‐AM as a frontline regimen for younger patients (≤65 years).